Strategi Pengembangan E-Tourism Sebagai Media Pemasaran Pariwisata di Taman Purbakala Kerajaan Sriwijaya - debby angely agustin (Departemen Pariwisata Universitas Negeri Padang, 2022)
This study determines local government strategies in e-tourism-based advertising in Sriwijaya Royal Park, Palembang City and reveals the factors that influence local governments in formulating e-tourism-based advertising strategies in Palembang City. This type of research is descriptive qualitative. Data were collected from interviews and analysis based on indicators of human resources, facilities and infrastructure, and human resources. Data collection techniques are carried out by observation (observation), interviews (interviews), and documentation. The results of this study indicate that the strategy of Palembang City in implementing e-tourism is maximized by forming a team filled with special abilities or skills to master IT. Especially in terms of the concept of e-tourism, physical means are limited, but technical knowledge requires technical funds, such as photographers and graphic design specialists. The supporting factor for e-tourism-based promotion in Palembang City is the organization's efforts and collaboration with various stakeholders to promote tourism in the Sriwijaya Royal Archaeological Park